Factors Influencing the Incidental Dose Distribution in Internal Mammary Nodes: A Comparative Study - Wang, Wei; Wang, Jinzhi; Qiu, Pengfei; Sun, Tao; Zhang, Yingjie; Shao, Qian; Xu, Min; Liu, Xijun; Li, Jianbin (Frontiers in Oncology, 2020)
Objective To investigate the effect of anatomic and technical parameters on the incidental internal mammary lymph node (IMN) irradiation (IIMNI) dose among postmastectomy patients. Methods We retrospectively delineated the IMN on planning CT images from 138 patients who had undergone postmastectomy radiotherapy (PMRT). We analyzed the IIMNI dose coverage and its relationship with anatomic and technical parameters. Results The IIMNI mean dose was 32.85±9.49 Gy, and 10 of 138 patients (7.25%) treated with PMRT received ≥ 45 Gy. In univariate analysis, the body weight, body mass index, body surface area, thoracic transverse diameter (DT), ratio of DT to the thoracic anteroposterior diameter (DAP), planning target volume of IMN (PTVIMN) included in PTV (IMNin) and the ratio of IMNin to PTVIMN (RIMNin) and PTV posterior border were the parameters affecting IIMNI dose. In multivariate analysis, body weight, DAP, DT, PTV volume, and RIMNin were correlative factors that affected IIMNI dose. Conclusions For patients who underwent PMRT without IMN irradiation (IMNI), there was a wide variety in IIMNI doses. A minority of patients had adequate IIMNI dose coverage, and the main factors influencing IIMNI dose coverage were patient anatomy and RIMNin.